2020
DOI: 10.1063/1.5120533
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high mechanical flexibility of 2D silicon telluride

Abstract: Silicon telluride (Si2Te3) is a two-dimensional material with a unique variable structure where the silicon atoms form Si-Si dimers to fill the "metal" sites between the Te layers. The Si-Si dimers have four possible orientations: three in-plane and one out-of-the plane directions. The structural variability of Si2Te3 allows unusual properties especially the mechanical properties. Using results from first-principles calculations, we show that the Si2Te3 monolayer can sustain a uniaxial tensile strain up to 38%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Previous work by Bletskan et al 22 indicated an indirect band gap value of 2.13 eV for crystalline Si 2 Te 3 at room temperature. Bhattarai et al 6 have also shown that the stress has a strong effect on the band gap energy as well as the nature of the transition (i.e., direct or indirect). Earlier work by Shen et al 5 also demonstrated an interesting variability of the Si 2 Te 3 band structures with respect to the orientation of the Si-Si dimers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work by Bletskan et al 22 indicated an indirect band gap value of 2.13 eV for crystalline Si 2 Te 3 at room temperature. Bhattarai et al 6 have also shown that the stress has a strong effect on the band gap energy as well as the nature of the transition (i.e., direct or indirect). Earlier work by Shen et al 5 also demonstrated an interesting variability of the Si 2 Te 3 band structures with respect to the orientation of the Si-Si dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Further, while Si 2 Te 3 material can be processed using standard semiconductor techniques, it is highly sensitive to the environment, which offers an advantage for chemical sensing applications 1,8 . Indeed, Si 2 Te 3 has one of the highest mechanical flexibilities among 2D materials ever reported 6 . Its interesting indirectdirect band gap transition with the application of mechanical uniaxial strain 6 and anisotropic optical dielectric properties 18,19 make this material even more interesting and provide promise for its potential applications.…”
mentioning
confidence: 99%
See 3 more Smart Citations